PREDIKSI PENJUALAN MELALUI METODE WEIGHTED MOVING AVERAGE (WMA) PADA UMKM “Nasi Bakar” - Riandi, Mariana Hakim; Wiyani, Natalia Titik; Arigawati, Desy (Jurnal Riset Entrepreneurship, 2024)
This study aims to find out the results of sales forecasting calculations using the Weight Moving Average method in Nurochmah Nasi Bakar MSMEs from April 2023 to July 2024. In addition, to determine the accuracy of forecast errors in sales forecasting calculations and the application of the Weighted Moving Average (WMA) method in predicting sales to Nurochmah MSMEs. The research method used is descriptive quantitative using historical sales data from January 2023 to July 2024, to predict sales using the WMA method at Nasi Bakar Nurochmah MSMEs from April 2023 to July 2024 using Production and Operations Management-Quality Control (POM-QM) software. The results of the calculation of sales forecasting using the WMA method on Nurochmah grilled rice MSMEs for April 2023 to July 2024 fluctuated as follows: December was 768.4 packs, a decrease of 4.547% from the actual 805 packs. January was 772.7 packs, a decrease of 0.553% from the actual 777 packs, February was 781.4 packs, an increase of 5.31% from the actual 742 packs. The accuracy of forecast error in calculating sales forecasting using the WMA method from April 2023 to July 2024 obtained an accuracy value of < 10% measured using the Mean Absolute Percent Error (MAPE). The average MAPE is 1.983%, it can be said that the forecasting ability of this method is very accurate. This shows that the WMA method can be applied to Nurochmah grilled rice MSMEs, so that it can help control sales volume, as well as as a basis for decision-making and planning sales targets for the next period.